“WAYS OF PREVENTING COMPLICATIONS AND RECURRENCES IN THE SURGICAL TREATMENT OF POSTOPERATIVE ANTERIOR ABDOMINAL WALL HERNIAS” - Muazzamov B.B; Khakimov M.Sh; Turaeva M.Sh; Muazzamov B.R; Rajabov D.R; Sadullayeva. Z (Scholar Express Journals, 2025)
As is known, the methods of anterior abdominal wall reconstruction used today undoubtedly have significant advantages and are continually being improved. However, despite these achievements, postoperative recurrences and complications are still observed with various techniques of hernioplasty, ranging from approximately 23% to 65%. According to the literature, clinical observations indicate that there is no definitive solution in selecting a surgical method for anterior abdominal wall hernias that can guarantee a 100% positive outcome. Modern alloplastic hernioplasty using synthetic biomaterials faces numerous challenges related to ensuring the reliability of surgical techniques and improving patients’ quality of life in both the early and long-term postoperative periods.
Keywords: Postoperative ventral hernias; hernioplasty; anterior abdominal wall hernia surgery